Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

log x + log (x-3) = 1

Sagot :

Given:

The logarithmic equation is:

[tex]\log x+\log (x-3)=1[/tex]

To find:

The value of x.

Solution:

Properties of logarithm used:

[tex]\log a+\log b=\log (ab)[/tex]

[tex]\log 10=1[/tex]

[tex]\log x[/tex] is defined for [tex]x>0[/tex].

We have,

[tex]\log x+\log (x-3)=1[/tex]

Using properties of logarithm, we get

[tex]\log [x(x-3)]=\log 10[/tex]

[tex]x^2-3x=10[/tex]

Splitting the middle term, we get

[tex]x^2-5x+2x-10=0[/tex]

[tex]x(x-5)+2(x-5)=0[/tex]

[tex](x-5)(x+2)=0[/tex]

[tex]x=5,-2[/tex]

In the given equation, we have a term [tex]\log x[/tex]. It means the value of x must be greater than 0 or positive. So, the only possible value of x is:

[tex]x=5[/tex]

Therefore, the value of x is 5.